Measurement of branching fractions of B decays to K-1(1270)pi and K-1(1400)pi and determination of the CKM angle alpha from B-0 -> a(1)(1260)(+/-)pi(-/+) - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2010)
We report measurements of the branching fractions of neutral and charged B meson decays to final states containing a K1(1270) or K1(1400) meson and a charged pion. The data, collected with the BABAR detector at the SLAC National Accelerator Laboratory, correspond to 454×106 BB̄ pairs produced in e+e- annihilation. We measure the branching fractions B(B0→K1(1270)+π-+K1(1400) +π -)=3.1-0.7+0.8×10-5 and B(B+→ K1(1270) 0π++K1(1400) 0π+)=2.9-1.7+2.9×10 -5 (<8.2×10-5 at 90% confidence level), where the errors are statistical and systematic combined. The B0 decay mode is observed with a significance of 7.5σ, while a significance of 3.2σ is obtained for the B+ decay mode. Based on these results, we estimate the weak phase α=(79±7±11)°from the time-dependent CP asymmetries in B0→a1(1260)±π decays. © 2010 The American Physical Society.